ANÁLISIS Y PROPUESTA DE UN MODELO DE VIRTUALIZACIÓN DE LA UNMSM. INNOVACIÓN, VIRTUALIZACIÓN Y FLEXIBILIZACIÓN CURRICULAR - Bedriñana Ascarza, Aquiles (2008)
As strategy for the process of Educational Modernization and Innovation of the Universidad Nacional Mayor de San Marcos (UNMSM), the dean of America, is imperative to undertake the process of virtualización of the University, with perspectives its universalization for a better world. The general objective of this study is the design of a model of virtualización to innovate the processes of eyewitness formation and of Experiences of Distance Education, as well as the activities of investigation and university extension in the UNMSM. One of the specific objectives of the project is the evaluation of pedagogical, economic, and technical factibility for the development of an electronic educational system (e-learning) in the UNMSM. First, we examine the current state, alternatives and perspectives of the virtual education in Peru, the advantages and disadvantages of e-learning as support of eyewitness and distance education. Besides, a study on the existing technologies in the market for the platforms selection process is carried out Learning Management System (LMS) and Contents Management (Learning Content Management System - LCMS), indicating the administrative, pedagogical, and technical requirements that should needs a technological platform. For the Progressive Virtualización of UNMSM a proposal of a pedagogical and organizational model is presented adequate to the reality of our alma mater.